1976
DOI: 10.1071/pp9760435
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte Leakage Induced by Chilling in Passiflora Species Tolerant to Different Climates

Abstract: A method was devised to measure chilling sensitivity in a series of species and hybrids of Passiflora having a range of climatic requirements. Leaves from plants which had been grown under 25°C day/18°C night were chilled at 0°C in the dark. At the same time, leakage of electrolyte from thin strips of these leaves was measured at 0°C using conductivity. Two main stages of leakage were found: a relatively slow rate (stage 1) which was followed by a high rate (stage 2), during which most of the electrolyte was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 0 publications
0
26
0
1
Order By: Relevance
“…Leaves of the type species P. edulis are able to withstand many days of chilling at OC without injury, but leaves of the closelyrelated P. edulis forma flavicarpa are injured after two or three d at 0° (15). Figure 3 shows that the more chilling-resistant passionfruit has a greater ability to recover catalase activity after chilling.…”
Section: Resultsmentioning
confidence: 94%
“…Leaves of the type species P. edulis are able to withstand many days of chilling at OC without injury, but leaves of the closelyrelated P. edulis forma flavicarpa are injured after two or three d at 0° (15). Figure 3 shows that the more chilling-resistant passionfruit has a greater ability to recover catalase activity after chilling.…”
Section: Resultsmentioning
confidence: 94%
“…A great deal of evidence has been accumulated to support this hypothesis (16,17). In addition, membranes may lose some of their semipermeability at temperatures below the phase transition point and become leaky (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Liebermann et aL (7) found 5 times as much potassium leakage from sweet potato roots after 10 weeks storage at chilling temperatures. There was also enhanced leakage of electrolytes from leaf tissue (3,11,19) and fruit tissue (16) at chilling temperatures. The results of Tatsumi and Murata (16) showed that fruit pitting, a symptom of chilling injury, was visible after 5 days whereas leakage did not increase until the 7th day.…”
mentioning
confidence: 99%